Prevention of cancer - McKinnell, Robert Gilmore; Bozzone, Donna M. (New York : Chelsea House, 2008)
Presents the latest research on factors believed to defend against cancer, major risk factors, and prevention tips
1. You are in control-well, mostly -- 2. Smokers are not necessarily stupid -- 3. Skin cancer-do not risk it! -- 4. Cervical cancer-preventable? -- 5. Childhood cancer survivors : a paradox -- 6. Breast cancer-preventable? -- 7. Diet and exercise do make a difference -- 8. A final word on prevention
Includes bibliographical references and index
Keywords: Cancer -- Prevention -- Popular works; Cancer -- Psychological aspects; Cancer -- Risk factors -- Popular works; Neoplasms